Srategi Pemasaran Pisang Pasir pada Home Industry Buk Lis di Kota Mojokerto - Pangesti, Salsabila Luki; Gemaputri, Ariesia Ayuning; Putra, Dhanang Eka; Pratama, Fredy Eka Ardhi (Jurnal Manajemen Agribisnis dan Agroindustri, 2023)
This research is motivated by the sand banana product which has been produced for a long time but is still a favorite product for teenagers. However, as time goes by, coupled with the development of technology, more and more business competitors are selling similar products, making sand banana products marginalized. The location of the Banana Pasir Buk Lis UMKM is located at Gang Gotong Royong No. 4, Mergelo, Balongsari, Magersari District, Mojokerto City. This research aims to: 1) Analyze internal and external factors in the marketing strategy of banana sand at the UMKM Pisang Pasir Buk Lis. 2) Determine and analyze appropriate strategies in the marketing strategy for banana sand at the UMKM Pisang Pasir Buk Lis. 3) Determine and explain the priority strategies of several alternative marketing strategies for banana sand at the UMKM Pisang Pasir Buk Lis. By using calculations, the data analysis method used in this research is conducting internal and external observations of the company which are examined through IFE and EFE, IE Matrix, SWOT Matrix and QSPM analysis to be able to determine alternative strategies. Based on the results of the QSPM calculation research, it was found that the main priority strategy was improving and maintaining product quality, taste and service with a TAS score of 6.96.